Banking Crisis Prediction: Emerging Crisis Determinants in Indonesian Banks - Musdholifah, Musdholifah; Hartono, Ulil; Wulandari, Yulita (International Journal of Economics and Financial Issues, 2020)
Many studies have been conducted in connection with revealing the determinants of a banking crisis but nothing addresses the exact causes of the crisis. This study aims at developing a model to discern a banking crisis prediction using Crisis and Default Index. The prediction was for 2015 to 2016 periods involving 21 variables that were classified into five major categories namely macroeconomic, internal banking condition, institutional quality, global aspect, and good corporate governance. Results showed that internal banking condition became the most influential factor toward the probability of existing banking crisis. Another finding depicted that management quality, ROE, BOPO, and LDR positively affected a banking crisis, therefore, the higher the values of the four elements, the higher the probability of the occurred banking crisis. Keywords: banking crisis, crisis determinants, causes of crisis JEL Classifications: E5, G2, H12 DOI: https://doi.org/10.32479/ijefi.9113